An integral-differential method for impedance determination of the hydrogen oxidation process in the presence of carbon monoxide in the proton exchange membrane fuel cell. (16th October 2020) - Darowicki, K.; Gawel, L.; Mielniczek, M.; Janicka, E.; Zielinski, A.; Mitzel, J.; Hunger, J.
Abstract: The impedance of a proton exchange membrane fuel cell powered by hydrogen contaminated with carbon monoxide, ranging from 150 to 300 ppb, is measured and discussed. The tested range of CO concentration complied with the fuel standard specified in the ISO standards. Studies of influence of CO contamination on operation of PEMFC are crucial for further development and commercialization of fuel cells for automotive applications. Based on the measurements made by Dynamic Electrochemical Impedance Spectroscopy (DEIS), changes in the cell impedance as a function of time were determined. An innovative integral-differential methodology for the analysis of chrono-impedance diagrams was developed, which enabled the extraction of the impedance spectra describing the anodic processes. This way of analysis is completely novel and original and it was not presented before in literature. The ability to monitor and diagnose the anode's operation under real operation conditions is demonstrated. The reversibility of the CO adsorption process and the loss of anode catalytic activity were verified. All this issues were not possible to be studied before with the use of classic impedance measurements. Highlights: Methodology for on-line monitoring of fuel cell performance. Effects of CO (in the range of 150–300 ppb) pollution of hydrogen stream. Determination of anode impedance changes exposed to very low concentrations of CO. Novel differential-integral analysis methodology of impedance determination.